Role of Diffuse Tensor Imaging in Predicting Outcomes of Decompressive Surgery in Degenerative Cervical Myelopathy—A Prospective Analysis - Neeraj Sharma; Rajesh Alugolu; Dinesh Gangapatnam; Mudumba Vijaya Saradhi (Indian Journal of Neurosurgery)
Background Cervical spondylotic myelopathy is a common degenerative disorder of the cervical spine. Assessing the severity of the disease objectively remains a challenge. Advances in magnetic resonance imaging (MRI), especially diffusion tensor imaging (DTI), elucidate the damaged or compressed fiber tracts in the cord. This study is our endeavor to correlate the relationship between clinical features, radiological features with special reference to DTI, and surgical outcome in patients with degenerative cervical myelopathy. Methods All consecutive patients of cervical spondylotic myelopathy and cord intensity changes in MRI, admitted and treated in the department of neurosurgery during the period of 2016 to 2018, were included and evaluated clinically and radiologically. The clinical evaluation included motor assessment scale (MAS), 30 meters walking, and hand grip. Radiological investigations included additional DTI in 3T MRI and clinical outcome was measured postoperatively after 12 months by modified Japanese Orthopedic Association (mJOA) recovery ratio and MAS scores. Results The patients age ranged from 30 to 80 years and the mean age of the study population was 55.95 ± 10 years. Patients with fractional anisotropy (FA) < 0.5 had higher grade of Nurick, that is, grade 5 in 4.3%, grade 4 in 65.2%, and grade 3 in 27.1% compared with grade 5 in 0%, grade 4 in 23.5%, and grade 3 in 47.1% in FA > 0.5. Mean mJOA recovery ratio in the group FA > 0.5 was 57.32 whereas it was 38.78 in FA < 0.5. Conclusion DTI serves as a potential biomarker for predicting the surgical outcome in degenerative cervical myelopathy cases and thereby making the surgical decision precise. FA can be a potential quantitative tool to predict the functional outcome following decompressive surgery for degenerative cervical myelopathy conditions, in particular lower FA values carries poor prognosis.